ФИЛАРХ, ПОЛИБИЈ И РАЗВОЈОТ НА ХЕЛЕНИСТИЧКАТА ИСТОРИОГРАФИЈА ВО III ВЕК ПР. Н. Е. (Philological Studies, 2019)
The subject of this paper is the development of the historiography in the early Hellenistic period, with a brief recapitulation of the problem of the so-called tragic history and the influence of rhetoric and philosophy on the 3rd century historiographers. The first problem that can not be overestimated is the fragmentary condition of the works from this period, which prevents us from forming a complete and final assessment of the value of these works. As to the question of the existence of tragic history as a separate sub-genre of ancient historiography, here the theory that practically it never existed is defended. On the other hand, while not denying the fact rhetoric and stylistic considerations in general played a greater role, the author warns that this does not mean that these works should a priori be relegated as inferior, i.e. that the historiographers were not interested in the truthfulness of the episodes that they were depicting. In the second part, the attention is turned towards Polybios’ criticism of the work of Phylarkhos; the conclusion being that even though Polybios’ attacks had more to do with his political affiliation rather than his theoretical criteria, nor were they always completely accurate, his evaluation, i.e. condemnation of Phylarkhos seems to be acceptable. What is perhaps more important is that this polemical digression clearly illustrates the shortcomings of Polybios himself, whose work and interpretations are all too often accepted without further analysis.
Keywords: hellenistic historiography, tragic history, Phylarkhos, Polybiоs